The usage of MDT in high-performance parasport - Michael ŠóŠ; Michaela Kotrbancová (Matej Bel University, 2021)
In this article we give arguments to support the usage of Mechanical Diagnosis and Therapy® (MDT) as a very suitable method for this difficult task. We do encourage the usage based on our recent intensive work with the paralympians. physiotherapist in any paralympic sport has to fulfill all the tasks his or her colleagues have with elite able-bodied athletes and in addition to that make sure that whatever disability the Paralympian has is not being worsened by the high-performance sport. We suggest MDT as a choice that has the capacity to fulfill the task. Mechanical Diagnosis and Therapy®, also known as the McKenzie Method, is one of the most evidence based non-invasive approaches to assessment and management of musculoskeletal disorders. The concept of MDT draws from symptomatic and mechanical responses of the patient's body during functional tests in positions, movements and repeated movements. Based on these responses is a clinician able to classify the problem and choose the appropriate treatment strategy. MDT uses the very same principles for the extremities that it uses for the spine. DOI: https://doi.org/10.24040/sjss.2020.6.2.23-29